Timing or Dosing of Intravenous Proton Pump Inhibitors in Acute Upper Gastrointestinal Bleeding Has Low Impact on Costs. (October 2016) - Lu, Yidan; Adam, Viviane; Teich, Vanessa; Barkun, Alan
Abstract : OBJECTIVES: High‐dose intravenous proton pump inhibitors (PPIs) post endoscopy are recommended in non‐variceal upper gastrointestinal bleeding (UGIB), as they improve outcomes of patients with high‐risk lesions. Determine the budget impact of using different PPI regimens in treating non‐variceal UGIB, including pre‐ and post‐endoscopic use, continuous infusion (high dose), and intermittent bolus (twice daily) dosing. METHODS: A budget impact analysis using a decision model informed with data from the literature adopting a US third party payer's perspective with a 30‐day time horizon was used to determine the total cost per patient (US2014) presenting with acute UGIB. The base‐case employing high‐dose pre‐ and post‐endoscopic IV PPI was compared with using only post‐endoscopic PPI. For each, continuous or intermittent dosing regimens were assessed with associated incremental costs. Deterministic and probabilistic sensitivity analyses were performed. RESULTS: The overall cost per patient is 11, 399 when high‐dose IV PPIs are initiated before endoscopy. The incremental costs are all inferior in alternate‐case scenarios: 106 less if only post‐endoscopic high‐dose IVs are used; with intermittent IV bolus dosing, the savings are 223 if used both pre and post endoscopy and 191 if only administered post endoscopy. Subgroup analysis suggests cost savings in patients with clean‐base ulcers who are discharged early after endoscopy. Results are robust to sensitivity analysis. CONCLUSIONS: The incremental costs of using different IV PPI regimens are modest compared with total per patient costs.